SUSPENSION OF BANKRUPTCY PROCESS IN RESIDENTIAL BUILDING COOPERATIVES AND PROBLEMS ENCOUNTERED (Third Sector Social Economic Review, 2016)
Cooperatives are organizations which do not seek profit and prioritize social objectives. For this reason, they have special position in countries economic and social structures. The type of cooperative, which is seen primarily in also our country, is residential building cooperative. While residential building cooperatives carry out their activities, like equity companies, they can fall into a situation where they fail to pay their debts and they can claim for suspension of bankruptcy. There exist some conditions in order to apply for suspension of bankruptcy and these conditions prevail for also residential building cooperatives. One of the conditions is to be deep in debt and the other is the existence of hope for recovery. Because of the distinctive features of cooperatives, some problems are confronted in residential building cooperatives in fulfilling these conditions. In this study, these problems and solution proposals are revealed.
Keywords: Residential Building Cooperatives; Suspension of Bankruptcy; Being Deep in Debt